Use of wire guided localization for resection of recurrent, oligometastatic gynecologic clear cell carcinoma to anterior abdominal wall - Hayley Womack; Fadi Abu Shahin; Edward Grendys (Elsevier, 2022)
We present the case of apparent oligometastatic, recurrent clear cell carcinoma in the abdominal wall. Due to central obesity, previous abdominal wall surgeries, and previous radiotherapy, the mass was non-identifiable by conventional surgical dissection. A wire guided localization technique placed preoperatively facilitated the identification and resection of the malignant nodule with negative surgical margins.